Effect of chronic heat stress on duodenal epithelial barrier integrity in low- and high-water-efficient broiler chickens - Liu, Lulu; Greene, Elizabeth S.; Roach, Brooklee; Orlowski, Sara; Dridi, Sami (Frontiers in Physiology, 2025)
Heat stress (HS) has long posed a significant challenge to the poultry industry due to its adverse effects, such as depressed feed intake, decreased growth performance, and increased water consumption. Water efficiency (WE, conversion of water intake into body weight gain), although often neglected, is a key economic and production trait that is significantly affected by HS. Recently, we selected two broiler lines for high WE (HWE) and low WE (LWE) and showed a differential hypothalamic expression of genes involved in water homeostasis regulation. As the gut also plays a significant role in water absorption, the present study aimed to determine the effect of chronic HS on duodenal barrier integrity in LWE and HWE broilers. Male HWE and LWE chicks (240 chicks/line) were individually wing-banded for line identification, weighed, and placed in 12 controlled environmental chambers (2 pens/chambers). On day 29, birds were subjected to thermoneutral conditions (TN, 25 °C) or cyclic HS conditions (HS, 36 °C for 9 h/day from 9:00 a.m. to 6:00 p.m.) (120 birds/line/environment) for 3 weeks. On day 49, duodenal tissues were collected for histological, biochemical, and molecular analyses. Hematoxylin and eosin (H&E) staining revealed that HS significantly reduced villus height in the duodenum. Further analysis using qPCR showed that the mRNA expressions of intestinal barrier integrity-related genes, including claudins (CLDN1, 4, 5, 8, 16, and 22), PALS1-associated tight junction protein (PATJ), gap junction alpha 1 and 3 (GJA1/3), cadherin 2 (CDH2), and catenin alpha 2 (CTNNA2), were significantly upregulated by HS, and this effect was more pronounced in the HWE line than in its LWE counterpart. The findings of this study indicate that HS induces duodenal morphometric alterations. Based on the reduced serum fluorescein isothiocyanate-dextran (FITC-D) levels previously reported in the HWE line, the increased abundances of CLDN, PATJ, GJA1, CDH2, and CTNNA2 mRNAs in the HWE line suggest an enhancement of its duodenal barrier integrity for better nutrient and water absorption and, consequently, better growth efficiency.